Immune repercussions in patients with functional dyspepsia: A systematic review (Research, Society and Development, 2021)
Introduction: Functional Dyspepsia (FD) is a chronic or intermittent stomach disorder due to loss of homeostatic balance, being part of Functional Gastrointestinal Diseases (FGIDs). Several factors can be involved with the disease and its immune repercussions. Objective: To evaluate, in patients with Functional Dyspepsia, the risk of immunological repercussions. Method: Systematic Literature Review. The data search strategy used was obtained through two databases: Biblioteca Virtual em Saúde (BVS) and PubMed. The guiding question follows the acronym PO, with P being patients with FD and O as immune repercussions. A combination of descriptors was used: “Dyspepsia” AND “Immune System”. The inclusion criteria used were any year of publication, in Portuguese and English, full online articles and Cohort and Cross-sectional studies that address the PO issue. After the initial identification of the articles, they were read in pairs and selected according to eligibility criteria. Results: Five articles were selected, with Cohort and Cross-sectional studies. In patients with FD, there is a greater probability of developing certain diseases caused by immune dysregulation, such as atopy and mood disorders. One of the main causal factors is inflammation caused by infections, in which stress has led to an increase in inflammatory cytokines throughout the body, which can lead to allergic conditions and neurological disorders. Conclusion: There was evidence of a correlation between FD and the onset of atopy and later mood disorders. However, it is necessary to invest in more articles to better elucidate the overlap between such diseases.